Effects of curing time and intensity and polishing technique on color stability of bleach-shade composite resins - Sedighe Sadat HashemiKamangar; Soheil Jafari; Marzieh Rouhaninasab (Wolters Kluwer Medknow Publications, 2023)
Background: Despite the improvements in optical properties of composite resins, their color stability is still a matter of concern. This study aimed to assess the curing time and intensity and polishing technique on color stability of bleach-shade composite resins. Materials and Methods: In this in vitro, experimental study, 128 discs (1 mm × 8 mm) were fabricated from two composite resins. The specimens fabricated from each composite were assigned to 8 subgroups (n = 8) based on the curing time and intensity and polishing with polishing points or discs. After polishing, the color parameters of specimens were measured by EasyShade spectrophotometer according to the CIEL* a*b* color system. The specimens were then immersed in tea solution, and their color parameters were measured again. Color change (ΔE) was calculated and analyzed at 0.05 level of significance. SPSS 25 was used for data analysis. Univariate four-way ANOVA was applied to assess the effects of composite type, curing time, curing intensity, and technique of polishing on ΔE of composite resins. Since the interaction effects were significant, subgroup analysis was performed by t-test. The level of significance for this test was set at 0.05. Results: The effects of curing intensity and polishing technique were significant on ΔE (P < 0.05). Filtek Z350 XBW composite specimens polished by polishing points experienced lower color change than those polished with discs. The minimum ΔE of Gradia XBW composite was recorded in specimens that underwent high-intensity curing for 20 s and were polished with polishing points while the maximum ΔE was recorded in specimens that underwent high-intensity curing for 20 s and were polished with discs. Conclusion: In all groups except on (Filtek, polishing with Disk, curing time = 20 s), high-intensity curing and polishing with polishing points were more effective and caused lower color change compared with low-intensity curing and polishing with discs.